DEMOGRAPHIC STATISTICS IN THE PERIOD OF THE WAR - SYNYUK, Nataliya (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Such a crisis phenomenon, with which Ukraine has been shaken for the rest time, has caused a lot of negative consequences. The demographic situation in Ukraine is turbulent with a lot of scientists and state leaders, by the way, is one of the most important problems of today. The rapidity of the number of people, the way of mass driving and temporary migration, the decrease in trivality and the hardness of life, the low level of nationality, all the traces of the war, the replication of such will be remembered. But we should signify that the very demographic crisis is an obstacle for the socio-economic development of all systems of the state, a threat to national security, as well as a threat to the development of international integration in the globalization of Ukraine. All the problems of the demographic crisis were foreseen by the statistical roses, as an effective tool for the identification of demographic transformation. Bringing demographic statistics up to international standards will allow us to establish economical barriers, create an international competitive market environment and protect national security. But on the face of it, the implementation of those appointed could be folded by the military camp of the state, and what is more important than the increase in mortality, migration and the loss of life. When the demographic crisis is observed in the wake of the full-scale invasion of Russia into Ukraine, the authors of the research have broken up the whiskers, which Ukraine is trying to overcome at the steepest camp. The consequences of the war on the side of demographic statistics will be irreversible, in the first place, it’s due to those who will go to war earlier, it’s a pity, less of the population will turn back from other lands, that hour will pass, people will step by step repair the regions of their lives. The onset of the last, a large-scale increase in the mortality rate among the young population, lads, as if fighting, it’s a pity that not all of them will turn back alive from the war, it’s immediately impacted by the nutrition of new generations. Based on the results of the follow-up, the authors discussed the theoretical basis for demographic statistics during the war. Current camp has become a way to analyze evidence in emigration and internal displacement. Directly further investigations would be able to show the expansion of mechanisms, as if they would help to mitigate the demographic impact on the economy of the country.